(untitled) (Studia Prawnicze / The Legal Studies, 1981)
The conciliatory settlement of labour disputes is one of the fundamental issues connected with the system of settling of disputes arising from labour contracts, which is now in force in Poland. The conciliatory settlement of labour disputes by the works and territorial arbitration committees and appeals committees for labour cases (eg. by organs decidinf in labour disputes in the 1st instancy) is based upon voluntary acceptance by the sides and the commissions of legal consequences arisings from legal and procedural acts of an employee and employer. Those acts can take a form of: the settlement, the withdroval by an ’employee of the petition starting the whole procedure, the renouncement or the limitation of the demand or the acceptance of workers’ demand by the employer - these acts, at the same time, constitute the forms of the conciliatory settlement of the dispute. By the ’mentioned acts, both sides either determine or create the rights and duties resulting from the contract of empoyment and decide about its duration. One of the most discussed problems of so understood disposition of legal rights by the sides is the definition of limits of workers’ concessions. These limits are marked by the labour law regulations settling the minimum of employees rights. It is not possible therefore for an employee to resign from the whole or a part of a demand put forward if such a resignation could leed to changes in the enmloyment contract less favorable than the minimum determin by the law. An important role in reaching of the settlement is played by the chairman and the adjudicative body of the commission deciding the dispute. The settlement of the dispute by the commission is preceded by a separate conciliatory procedure in which the chairman of the commission occurs as a sui .generis mediatory organ. After the seatting is started the duty to undertake at each stage of the proceeding endeavours to persuade the parties to reach an agreement removing the causes for the dispute, is placed with the adjudicative body. The freedom of tides to command .the subject of the procedure is restrained by the right as well as the duty of the chairman and the commission itself to control the actions ending the negotiations. If the settlement, withdrawal of the petition, renouncement or limitation of the demand violates the law or the rules of social life - the commission express its veto and the procedure is continued until the adjudicative body decides the fundamental issues of the dispute. However, the groundless acceptance by an employer of the workers demands is omited by the adjudicative body. Thus the protection of founded social and legal interests of sides is strengthened, particularly the interests of the employee.